RITUAL PUBLIK PADA MASYARAKAT DESA PULAU BUSUK JAYA KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI (STUDI KASUS DOA PEKUBURAN) - Oktizalvi, Wahyuni; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research entitled "Public Rituals In The Village Community Busuk Jaya District Inuman Kabupatem Kuantan Singingi (Case Study Do'a Cemetery)". The research was conducted at Busuk Jaya Village, Inuman Subdistrict of Kuantan Singingi Regency, whose purpose was to know how the Ritual Prayer of the Cemetery and its function and value system were applied. The method used in this research is Qualitative Descriptive research method, that is the research discussion is presented and analyzed in the form of description of words (description) with qualitative approach. This research is also supported by the implementation of in-depth interviews with the informants who have been established first by the researchers. So the results of these interviews obtained information that is very supportive for the validity of the data that became the focus of this study. Based on the results of the research, in this ritual there are some important things that are divided into two implementation of Prayer Ritual of Cemetery itself, that is the implementation of cemetery prayer in the pilgrimage of grave, as well as the implementation of Prayer Cemetery in the tribal house association of tribe. The Cemetery Prayer Ritual is held once every year, on the sixth day of Eid or six Syawal. Implementation begins at eight o'clock in the morning until the end, with the aim of pilgrimage and gathering each other between tribes respectively. The function of Rtiual Prayer This cemetery in pilgrimage is to pray for the salvation of the deceased family, and the second function of the Cemetery Prayer in the assemblies of the tribal aims to cultivate the relationship between the nephew's children in order to adapt to their fellow human beings to introduce the customs. And the value system of Ritual Prayer Cemetery consists of several aspects depicted on Historical Value, Religious Value (Religious) and, Family Value (Hospitality).Keywords: Ritual, Prayer, Cemetery, Pulau Busuk Jaya